PERAN WORLD TRADE ORGANIZATION (WTO) SEBAGAI BASIS KERJA SAMA PERDAGANGAN INDONESIA PADA ASEAN FREE TRADE AREA (AFTA) - Halifa Haqqi, Abdullah William Rasyidin, Christy Damayanti & (Transformasi, 2016)
This study, entitled " The World Trade Organization (WTO) Roles As Basis Indonesia TradeCooperation In The ASEAN Free Trade Area (AFTA). Background in international tradeliberalization with presence of free trade in a country, the World Trade Organization (WTO)was born for the world trade. In this casethe WTO roles as an instrument, arena, and actor formultilateral trade, regional, and national levels. This study aims to explain the World TradeOrganization (WTO) roles as basis Indonesia trade cooperation in the ASEAN Free Trade Area(AFTA) using international organizations and regionalisms theory. The research usedqualitative research with primary data sources and secondary data. The primary data usingwords and actions of the informant, while secondary data from scientific books, theses, journals,government reports, magazines, archive important trade-related sheets, and a valid website.Data collection techniques authors select document, archive footage, interviews, andparticipant observation. Data analysis techniques with data reduction, data presentation, andconclusion / verification data. These results indicate that the WTO roles is a basis of makingpolicy multilateral trade, regional AFTA, national and Indonesia that trade policy as basis forIndonesia trade in realizing national interests with reference to approval of the WTO as a legalumbrella trade and strengthen trade cooperation AFTA.Key words: the WTO roles, AFTA, Trade Policy,Basis Indonesia Trade cooperation